The Role of Principals as a Manager and Supervisor in Improving Academic Quality in Vocational High School - Muhamad Ghozin; Maryanto; Ghufron Abdullah (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This study examines the role of school principals as managers and supervisors in improving academic quality at SMK Negeri 1 Sale, Rembang Regency. Using a qualitative approach, data were collected through interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings highlight the principal’s role in designing academic programs, managing resources, and fostering a conducive learning environment. As a supervisor, the principal provides guidance and evaluation to enhance teachers’ pedagogical competence. Effective academic supervision leads to improved teacher performance and student achievement. The success of this process relies on communication and support from all school stakeholders. The study concludes that strengthening the principal's leadership and supervisory skills should be prioritized in educational policies. Keywords: Principal; Manager; Supervisor; Academic quality